Creative destruction and regional productivity growth: evidence from the dutch manufacturing and services industries - Niels Bosma; Erik Stam; Veronique Schutjens (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Do firm entry and exit improve the competitiveness of regions? If so, is this a universal mechanism or is it contingent on the type of industry or region in which creative destruction takes place? This paper analyses the effect of firm entry and exit on the competitiveness of regions, measured by total factor productivity (TFP) growth. Based on a study across 40 regions in the Netherlands over the period 1988-2002, we find that firm entry is related to productivity growth in services, but not in manufacturing. The positive impact found in services does not necessarily imply that new firms are more efficient than incumbent firms; high degrees of creative destruction may also improve the efficiency of incumbent firms. We also find that the impact of firm dynamics on regional productivity in services is higher in regions exhibiting diverse but related economic activities.
Keywords: L10; M13; O18; R11; 330; Firm entry; firm exit; turbulence; regional competitiveness; total factor productivity; Innovationswettbewerb; Markteintritt; Marktaustritt; Regionale Entwicklung; Internationaler Wettbewerb; Produktivität; Branchenentwicklung; Schumpeterismus; Schätzung; Niederlande